Overview of Dengue Hemorrhagic Fever (DHF) Prevention in The Community Health Center - Asishe; Ismarina; Martha Ikhlasiah; Prihayati (KHD-Production, 2024)
Dengue hemorrhagic fever is an infectious disease caused by the dengue virus and transmitted through the mosquito vector of the Aedes aegypti species. Dengue fever is an endemic disease in more than 100 countries. World Health Organization (WHO) data shows that the number of reported cases of dengue fever has increased more than 8-fold over the last 4 years, from 505,000 cases to 4.2 million in 2019. Based on the Indonesian Health Profile, dengue cases were reported in 2020, and 108,303 cases were recorded in Indonesia. In line with the number of cases, deaths due to dengue fever in 2020 were 747 deaths. In Banten Province, in the last 3 years, there have been dengue fever cases: in 2020, there were 3,132 cases, in 2021, there were 3,125 cases, and in 2022 it fell to 2,798 cases. In January 2024, it reached 1,619 cases; in February 2024, it increased again to 1,933 cases. The method of preventing dengue fever is considered very effective and relatively cheaper compared to previous methods. This method is recommended to the public, namely by carrying out 3M plus activities, namely closing water reservoirs, draining water reservoirs, and burying used items that can collect rainwater. Another way to repel or avoid mosquito bites is by using anti-mosquito medication or spraying with insecticide. This research aims to analyze the effect of health interventions on dengue prevention. The design of this research is cross-sectional. The population in this study was the community in the working area of ​​the Waringinkurung Community Health Center, Serang Regency. The sampling method used in the research is the total sampling technique. The Chi-Square test results show a relationship between knowledge, attitudes, perceptions, availability of health infrastructure, cadre support, and 3M behavior toward preventing dengue fever